Temporary Agency Workers—Precarious Workers? Perceived Job Security and Employability for Temporary Agency Workers and Client Organization Employees at a Swedish Manufacturing Plant - Håkansson, Kristina; Isidorsson, Tommy (Nordic Journal of Working Life Studies, 2015)
The vulnerable situation of temporary agency workers is manifested in previous research that evidences the job insecurity of this group. However, research shows that this insecurity is due to the temporary nature of employment contracts for this group of workers. In Sweden, where temporary agency workers have the same type of employment contracts (i.e., temporary or permanent contracts) and are entitled to the same employment protection as other groups of employees, one might expect a different picture. This article examines the situation of temporary agency workers who have the same working conditions as client organization employees. These workers have permanent contracts and are treated like client organization employees. We have chosen to examine this case because we anticipate it to be very likely to contradict statements regarding temporary agency workers’ affiliation with the precariat. This article aims to empirically elucidate the precariousness of temporary agency workers who are highly integrated with client organization employees and who share the same work tasks. Our analysis shows that competence development is crucial to perceptions of job security. However, temporary agency workers lack competence development, both on the part of the employer (the temporary work agency) and on the part of the client organization. The client organization has no incentive to invest more than the required competencies, since temporary agency workers only constitute a buffer in case of a downturn. We argue that it is the agency workers’ connection with a buffer that results in a lack of job security. Our results also show that temporary agency workers’ job security could be increased if temporary agencies were to invest in competence development for the agency workers, thus overcoming these workers’ vulnerability in constituting a buffer.